Clinical immunology - Rezaei, Nima (Academic Press, 2023)
Clinical Immunology not only introduces the reader to the human immune system, it also covers immunology from clinical manifestation to therapeutic approaches in a wide range of conditions. Each chapter describes an introduction, the clinical manifestations, the immunopathogenesis, diagnosis, lab tests and therapeutic approaches. The book guides clinicians, researchers and students to a better understanding of the matters of immunologic-based diseases that can lead to better decision-making for patients. Because of the growing knowledge regarding the function of immune system in health and disease conditions, clinicians, researchers and students increasingly require an exclusive scientific reference to guide them on matters of immunologic-based diseases. Accordingly, despite the existence of numerous high quality references in basic and cellular/molecular immunology which deeply explain different immunologic mechanisms, there is still a knowledge gap in the field of clinical immunology.